Learning how planarization can affect dichroic patterns in polyfluorenes. Issue 5 (11th March 2020) - Pietropaolo, Adriana; Nakano, Tamaki
Abstract: The circular dichroism spectra of a single chain of polyfluorene was predicted for a p ‐twisted helix conformation and local planarized polymer sections in the presence and in the absence of thermal vibrations. Under thermal vibrations at 300 K, the planarized section of polyfluorene affords a red‐shifted positive dichroic band between 446 and 456 nm, preserving a degree of chirality. The S1 ← S0 excitation energy decreases from 3.29 eV, for the p ‐twisted helix to 2.77 or 2.71 eV, for planarized sections with one or two coplanar twists, respectively. Thermal vibrations and intramolecular rotations eventually affect the circular dichroism spectrum patterns, where planarized bent conformers induce a positive band towards 450 nm. Abstract : DFT calculations predict distinctive CD spectral patterns for p ‐twisted and planar conformations of polyfluorenes sampled from enhanced sampling simulations, which are believed to be involved in helix formation to the polymer by circularly polarized light. P ‐twisted conformation features an excitonic coupling identified by one positive and one negative rotational strengths between 350 and 375 nm, while planar conformations by positive rotational strengths between 450 and 475 nm.